Acetilholinesteraza v električno draženi denervirani mišici extensor digitorum longus podgane - Bartolić, Andrej (Medicinski razgledi, 2001)
Background. The basis for the function of the nervous system is signalling among the nerve cells through the synapses. Normal signalling requires precisesynthesis and localisation of synaptic structures within the cell. There is a lot of work done in this field and the most often used model for the research is the neuromuscular junction because of its accessibility. The enzyme acetylcholinesterase (AChE) plays a crucial role in it by degrading acetylcholine and by that stopping the electrical signal among the nerve cells. The activity and localisation within the cell are very important for the proper function of the AChE. They depend on the expression of the AChE gene, which is further dependant on many factors and their inter-relationship.Among them, the most important are electromechanical activity and local neural mediators. Denervation of the muscle causes a lack of the factors mentioned above and consequently leads to atrophic changes of the muscle, decrease of the AChE activity in neuromuscular junction and the level of AChE mRNA in the muscle cells. Aim. and hypothesis. Our observations were based, on the measurement of the AChE activity and the level of AChE mRNAin the fast rat extensor digitorum longus (EDL) muscle. We used different stimulation patterns on the animal model. The results were then compared in order to test the next hypothesis. Change in the evel of AChE mRNA and the activity of AChE in the EDL muscle after denervation can be partially prevented by a specific simple pattern of electrical muscle stixnž ulation. (Abstract truncated at 2000 characters)
Keywords: fiziologija; Muscle, skeletal; mišice; Muscle denervation; Electric stimulation; električna stimulacija; Acetylcholinesterase; Analysis; Rats